Heat flux and skin friction on surface of a cone in supersonic flows - Ng, Jun Yang. (2011)
Empirical formulation and CFD simulations were carried out to investigate the skin friction and heat flux on a conical wall surface. Empirical mathematical models were formulated based on Blasius flat plate flows and corrected for compressible conical flows. The empirical models were extended to include transition onset locations based on experimental data. A 2D axisymmetric mesh was developed and the CFD flow solver FLUENT was used to solve for the wall shear stress and surface heat transfer rate. The results were compared against the empirical models and correction factors based on statistical interpolation were introduced to align the empirical and CFD models. For all of the CFD simulations, the two-equation SST k-w ￼and four-equation transition SST models were used. A database consisting of all the results simulated by CFD and empirically was compiled. Further experimental-based investigation is required to verify the accuracy of the transition onset locations simulated.